Enhancing English Learning Through Interactive Call: A Multimodal Approach at SMAN 1 Enrekang - Hasnur; Sangkala, Ismail; Hambali, Uyunnasirah (FKIP Unismuh Makassar, 2025)
This study investigates the impact of a Computer-Assisted Language Learning (CALL) model with a multimodal approach on students’ motivation to learn English at SMAN 1 Enrekang. Using a true experimental design, 60 tenth-grade students were purposively selected and divided into experimental and control groups. Data were collected through pre-tests, post-tests, and motivation questionnaires, then analyzed using paired t-tests and linear regression via SPSS 26. Results revealed a significant increase in both learning outcomes and motivation in the experimental group, with post-test scores rising from 62.50 to 80.5, and motivation scores averaging 51.30—categorized as high. In contrast, the control group showed a decline in performance and lower motivation levels. The findings highlight the urgent need for innovative, tech-integrated teaching methods in language education. This study contributes by demonstrating that multimodal CALL is not only effective but also a practical alternative to conventional instruction for enhancing English learning engagement and outcomes.